Legendary intertextuality in the novels of Hani Al-raheb. - Nasser, Siham; Alloush , Amani (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The research claims to tackle the openness of the Syrian narratives to the humane narrative heritage in the light of intertextuality theory which handles the production of texts and their relations to the historical contexts as well as their contemporary surroundings.According to the position the legend occupies in all life fields , the robust relation between the legend and literature , as well as Hani Alraheb’s will to construct new imaginary narrative worlds that deviate toward what is legend like ,his literary texts witnessed the presence of Arabic ,Greek and Roman legends via textual relations that opened new horizons of reading , interpretation and memory recollection for the reader. Despite the available opportunities to study other products of contemporary Arabic narratives , the signification of the position Hani Alraheb occupied and still in the map of creativity in Arabic narratives , his method of perceiving the legend theme in his texts, particularly narratives so as to trace the lines by which such a presence abides , its techniques and signification.